Analisis Manajemen Risiko Pada Agen Brilink: Studi Kasus Di BRI Unit Wirolegi Jember - Rifni Miftahur Rohmah; Rani Maulidasari; Wafiq Nur Azizah (STIKes Ibnu Sina Ajibarang, 2024)
BRI Bank BRI Agent has become an integral part of the Indonesian government's efforts to increase financial inclusion across the country. This research investigates the risks, role and impact of BRILink agents in expanding access to financial services for the community, especially in remote areas and difficult to reach by conventional financial institutions. Through a qualitative approach involving in-depth interviews and secondary data analysis, this study describes various important aspects related to BRILink agents, including the distribution network, services provided, challenges faced, and their impact on financial inclusion. The findings show that BRILink agents have succeeded in expanding the reach of banking services, facilitating financial transactions, and increasing financial literacy among previously underserved communities. However, challenges such as limited technological infrastructure, high operational costs, and lack of awareness of the benefits of financial services are still obstacles that need to be overcome. Based on the results of this research, it is recommended that the government, regulators and other related parties continue to support and improve the BRILink agent ecosystem through supportive policies, structured training and continuous technological innovation. Thus, BRI Bank BRI agents have significant potential in realizing wider and more sustainable financial inclusion in Indonesia.